An information privacy culture instrument to measure consumer privacy expectations and confidence. (9th July 2018) - Da Veiga, Adéle
Abstract : Purpose: This paper aims to propose an information privacy culture index framework (IPCIF) with a validated information privacy culture index instrument (IPCII) to measure information privacy culture across nations. The framework is based on consumers' privacy expectations, their actual experiences when organisations process their personal information and their general privacy concerns. Design/methodology/approach: A survey method was deployed to collect data in South Africa – the first participating country in the study – to start building a global information privacy culture index (IPCI) and to validate the questionnaire. Findings: The IPCI revealed that there seems to be a disconnect between what consumers expect in terms of privacy and the way in which organisations are honouring (or failing to honour) those expectations, which results in a breach of trust and the social contract being violated. Practical implications: Governments, information regulators and organisations can leverage the results of the privacy culture index to implement corrective actions and controls aimed at addressing the gaps identified from a consumer and compliance perspective. The validated IPCII can be used by both academia and industry to measure the information privacy culture of an institution, organisation or country to identify what to improve to address consumer privacy expectations and concerns. Originality/value: The IPCIF and validated IPCII are the first tools that combine the concepts of consumer expectations and their confidence levels in whether organisations are meeting their privacy expectations, which are in line with the fair information practice principles and the privacy guidelines of the Organisation for Economic Cooperation and Development, to determine gaps and define improvement plans.